Close action and long action as essential characteristics of interaction in the plane of international relations - Харченко, Ю. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
In the article on the basis of socio-philosophical analysis the conceptualization of the phenomena of close actions and long actions as mechanisms for strategic interaction in the plane of international politics is carried out. The phenomenon of interaction is presented as influencing the functional characteristics of social ties and substantially reflecting the peculiarities of constructing public relations, generating opportunities for the establishment of more or less strong ties.